2022
DOI: 10.3389/fphar.2022.852858
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Activation Enhances Lipid Accumulation During Adipocytes Differentiation Through Suppressing the Expression of Sirtuin-3, Sirtuin-5, and Browning Genes

Abstract: P2X7 signaling has been explored in adipose tissue because of its potential to promote ATP-activated inflammatory cascades during obesogenic environments. However, limited literature has investigated the role of the P2X7 receptor in lipid metabolism during adipocyte differentiation. This study sought to explore the regulatory roles of P2X7 in adipocytes. This study utilized the in vitro 3T3-L1 differentiation model. Lipid accumulation, intracellular triglyceride, and extracellular glycerol were determined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…On the other hand, knockout models of P2X7 showed a reduction in the expression of CCL2 and IL6 in WAT, but no alterations were observed in BAT thermogenesis [110]. In adipocytes, it has been observed that the expression of P2X7 is related to an inhibition of SIRT3/5 genes involved in browning, favoring the adipogenesis process [111]. Therefore, it is possible that the expression of P2X7 generates muscle atrophy, increases adipogenesis, and reduces BAT, contributing to the development of obese sarcopenia in chronic inflammation.…”
Section: P2 Receptors In Muscle and Fat In Sarcopeniamentioning
confidence: 99%
“…On the other hand, knockout models of P2X7 showed a reduction in the expression of CCL2 and IL6 in WAT, but no alterations were observed in BAT thermogenesis [110]. In adipocytes, it has been observed that the expression of P2X7 is related to an inhibition of SIRT3/5 genes involved in browning, favoring the adipogenesis process [111]. Therefore, it is possible that the expression of P2X7 generates muscle atrophy, increases adipogenesis, and reduces BAT, contributing to the development of obese sarcopenia in chronic inflammation.…”
Section: P2 Receptors In Muscle and Fat In Sarcopeniamentioning
confidence: 99%